Financial Health and Financial Distress: The Moderating Role of Firm Size in Islamic Banks (2021–2023) - Isna Putri Adilah; R. Melda Maesarach (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
The purpose of this study is to use the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) technique to examine the financial health of Indonesian Islamic commercial banks from 2021 to 2023. Firm size is used as a moderating variable for financial distress. Using secondary data from Islamic commercial banks' annual financial reports, the investigation looked at the correlations between the variables using moderation regression methods. The findings indicate that while the Operational Cost to Operational Income Ratio (CIR) has a large favorable impact on financial hardship, the Capital Adequacy Ratio (CAR) has a considerable negative impact. However, as their values are below the table, Non-Performing Financing (NPF), Good Corporate Governance (GCG), Financing to Deposit Ratio (FDR), and Return on Assets (ROA) have no discernible impact. The association between financial hardship and NPF, GCG, and ROA is moderated by firm size, but not by other factors. The model well describes the variability of financial hardship, as evidenced by the determination coefficient of 91.6%. This study highlights the importance of firm size in mitigating financial distress and offers insights for regulators and bank management to enhance financial performance and reduce financial distress risks.